2016
DOI: 10.1007/s11356-016-7036-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sulfathiazole degradation by persulfate in Milli-Q water and in effluent of a sewage treatment plant

Abstract: The presence of antibiotics and their metabolites in natural waters has raised some concern among scientists around the world because it can lead to bacterial resistance and other unknown consequences to mankind and wildlife. Persulfate (PS)-driven oxidation is a new technology that has been used successfully to remediate contaminated sites, but its use to treat wastewater, especially sewage treatment plant (STP) effluent, is still scarce. This paper describes the effect of several persulfate activation method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Although sulfate radicals have a lower redox potential than hydroxyl radicals, they are more selective towards certain organics (Velosa and Nascimento 2017;Zhou et al 2017;Lutze et al 2015), and this may justify the reactivity recorded at lower pH values, where sulfate radicals prevail. Dhaka et al (2017) reported that the UV-activated persulfate degradation of methyl paraben at pH = 9, where hydroxyl radicals were the dominant species, was lower than at pH = 3 or pH = 6.5, where sulfate radicals prevailed.…”
Section: Ln Co=cmentioning
confidence: 99%
“…Although sulfate radicals have a lower redox potential than hydroxyl radicals, they are more selective towards certain organics (Velosa and Nascimento 2017;Zhou et al 2017;Lutze et al 2015), and this may justify the reactivity recorded at lower pH values, where sulfate radicals prevail. Dhaka et al (2017) reported that the UV-activated persulfate degradation of methyl paraben at pH = 9, where hydroxyl radicals were the dominant species, was lower than at pH = 3 or pH = 6.5, where sulfate radicals prevailed.…”
Section: Ln Co=cmentioning
confidence: 99%
“…Nonetheless, differing results like ours were already reported in the literature. For instance, Velosa and Nascimento (2017) have also reported similar results for sulfathiazole degradation present in STP effluent promoted by activated persulfate. Furthermore, there are already evidences in the literature mentioning that the addition of carbonates to activated-persulfate systems can generate reactive carbonate species capable of catalyzing the propagation reactions, resulting in more sulfate radicals (BENNEDSEN; MUFF; SØGAARD, 2012), which would explain the higher AMZ degradation observed in mineral water.…”
Section: Influence Of Inorganic Constituents Of Natural Waterssupporting
confidence: 55%
“…The presence of medicines, their metabolites and/or their degradation products, is a current problem. 194 The photodegradation of sulfathiazole in aqueous media under visible light irradiation ( λ > 400 nm) was studied by Yang and co-workers. 195 They used well-faceted TiO 2 nanosheets with coexposed (001) and (101) and deposited selectively on α-Fe 2 O 3 and Fe/Co–N 4 on (001) facets (NTiO 2 –NS).…”
Section: Photocatalytic Degradation Of Organic Pollutantsmentioning
confidence: 99%